1984
DOI: 10.1111/j.1365-2125.1984.tb04996.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ICI 118,587 and atenolol on the responses to exercise and on breathlessness in healthy subjects.

Abstract: 1 The effects of ICI 118,587 and atenolol on the responses to submaximal exercise and on breathlessness were studied in six healthy subjects. Atenolol reduced heart rate at rest and during exercise whereas ICI 118,587 increased resting heart rate but caused a small reduction in the highest heart rate achieved during exercise. 2 Neither ICI 118,587 nor atenolol significantly changed minute ventilation or oxygen uptake either at rest or during exercise. There were no effects on bronchomotor tone. 3 The assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…As has been stressed previously, this validation is an important part of studies examining the effects of drugs on breathlessness and has usually been an integral part of the experimental design O'Neill et al, 1984). In the present study, it has been shown that the validation can be performed at a single session.…”
Section: Discussionmentioning
confidence: 69%
“…As has been stressed previously, this validation is an important part of studies examining the effects of drugs on breathlessness and has usually been an integral part of the experimental design O'Neill et al, 1984). In the present study, it has been shown that the validation can be performed at a single session.…”
Section: Discussionmentioning
confidence: 69%
“…The purpose of this study was to investigate the effects of xamoterol, a partial 1l-adrenoceptor agonist (Nuttall & Snow, 1982;Rousseau et al, 1983) on lung function, HR and BP in comparison with placebo and atenolol, a 1ladrenoceptor-selective antagonist (Ellis et al, 1981;Lammers et al, 1985). Xamoterol acts as a P-adrenoceptor agonist at low levels of sympathetic tone, but as a P-adrenoceptor antagonist when sympathetic tone is high, as during exercise (Harry et al, 1981;Rousseau et al, 1983;O'Neill et al, 1984). As we were interested to see whether xamoterol had any effect on lung function in view of its intrinsic sympathomimetic activity, the patients were studied at rest.…”
Section: Discussionmentioning
confidence: 99%
“…Xamoterol acts as a P-adrenoceptor agonist at low levels of sympathetic tone, but as a P-adrenoceptor antagonist when sympathetic tone is high, as during exercise (Harry et al, 1981;Rousseau et al, 1983;O'Neill et al, 1984). As we were interested to see whether xamoterol had any effect on lung function in view of its intrinsic sympathomimetic activity, the patients were studied at rest.…”
Section: Discussionmentioning
confidence: 99%
“…Some support for a role for J receptors being involved in breathlessness during exercise in normal subjects emerged from a study of ~-adrenoceptors. An antagonist increased breathlessness during exercise and this could not be attributed to a change in bronchomotor tone [12). It is possible, that a reduction in cardiac contractility caused a rise in pulmonary capillary pressure with associated stimulation of J receptor activity.…”
Section: Interventions Affecting Respiratory Drives: Role Of the Vagusmentioning
confidence: 93%